Music Academies Management in Greece - Dimitriadis, Aristotelis; Kefalaki, Margarita (International Conference on Business and Economics - Hellenic Open University, 2025)
Music performance in Greece should be set up as an independent field of study instead of its current status as part of Musicology. This is actually what we prove in this academic study, identifying the important role of Music Academies. Despite the repeated calls of the music community for the creation of a Music Academy, the successive Greek Governments do not seem to recognize this educational gap. At the moment there isn’t any Music Academy in Greece. Consequently, young musicians who wish to complete their studies in music performance are obliged to study abroad. This paper highlights the lack of Music Academies as a deficit of Greek higher education, analyzing the advantages of their creation. More specifically, this study specifies some needed management steps for the development of music academics with the help of a questionnaire submitted to a carefully selected sample audience, a SWOT analysis and interviews with well-known music professionals. The study programs of the Royal Music Academy in London and the Music Academy in Ankara are also examined as potential analogues. Based on the data collected, the curriculum in Greek higher education should be revised to adapt to the new educational and societal needs. Finally, Music Academies should be created following an adequate managerial approach. JEL Classifications: M11, M14, I20, I23 Keywords: Music Academies, Cultural Management, Greek Higher Education